2012
DOI: 10.1080/09518398.2011.590158
|View full text |Cite
|
Sign up to set email alerts
|

Actively navigating the transition into college: narratives of students with learning disabilities

Abstract: Students with learning disabilities (LD) are particularly vulnerable in making the school-to-college transition where they negotiate a complex constellation of challenges that include academic demands, social expectations, and emotional/ personal growth. Although a substantial body of knowledge exists about college students with LD, it is largely predicated upon both extrinsic supports available to ensure a successful transition into college and ways to maintain that success. In contrast, intrinsic knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
2
10
0
2
Order By: Relevance
“…Stokes, Newton, and Kaur (2007) described how symptoms related to social interactions persist throughout adult life, even for high-functioning individuals with autism. In accordance, college students with ASD in previous qualitative studies reported social problems, and a deep sense of feeling different and isolated (Connor, 2012; Gelbar et al, 2014; Griffin & Pollak, 2009; Jones, Huws, & Beck, 2013; Ryder, 2017; Stoddart, 2005).…”
Section: Discussionsupporting
confidence: 68%
“…Stokes, Newton, and Kaur (2007) described how symptoms related to social interactions persist throughout adult life, even for high-functioning individuals with autism. In accordance, college students with ASD in previous qualitative studies reported social problems, and a deep sense of feeling different and isolated (Connor, 2012; Gelbar et al, 2014; Griffin & Pollak, 2009; Jones, Huws, & Beck, 2013; Ryder, 2017; Stoddart, 2005).…”
Section: Discussionsupporting
confidence: 68%
“…College students, especially those that have lived with executive functioning difficulties, may encounter the additional step of whether to self-advocate for disability accommodations on campus, to receive updated testing to reconfirm their diagnosis, or even begin to grapple with the potential adult diagnosis of a learning disability (Connor, 2012). Broadly, executive functioning relates to the mind's ability to organize, prioritize, and manage details that aid in daily functioning (Barkley, 2012).…”
Section: Introduction: Mindfulness As An Intervention For Executive Fmentioning
confidence: 99%
“…Sin embargo, estudios anteriores apuntan hacia resultados opuestos, es decir, las mujeres tienen mejores resultados académicos en la universidad que los hombres (Rodríguez, Fita y Torrado, 2004), lo que se debe a mayor capacidad de esfuerzo, hábitos de estudio y de sobreponerse a situaciones adversas. En todo caso, indican la necesidad de mayor aporte preventivo por parte de la Universidad en proveer apoyos específicamente a los estudiantes de estas titulaciones, ampliando la oferta y la información sobre servicios de orientación que ayuden al colectivo con sus dificultades académicas (Connor, 2011).…”
Section: Discusión Y Conclusionesunclassified